Boosting innovation in Europe - Mathias Dewatripont; Bruno van Pottelsberghe de la Potterie; André Sapir; Reinhilde Veugelers (Bruegel, 2010)
Innovation is key to the future of Europe. This Policy Contribution, written together by Mathias Dewatripont, Solvay Brussels School of Economics and Management; Bruno van Pottelsberghe and André Sapir, Senior Fellows at Bruegel and professors at ULB; and Reinhilde Veugelers, senior fellow at Bruegel and professor at Katholieke Universiteit Leuven, makes suggestions based on three principles: to give primacy to merit-based selection of projects at the European level, to strengthen the single market to make it conducive for research and innovation and to remove barriers that hinder dynamic restructuring. This paper is addressed to the July 2010 informal Competitiveness Council (Research) under the Belgian Presidency.
Keywords: 330; Innovationspolitik; Europäische Forschungs- und Technologiepolitik; EU-Staaten